Informed aesthetic consensus and the creation of urban environments - Mueller-Salo, Johannes (Polskie Studia Krajobrazowe, 2019)
The aim of this paper is to analyze the aesthetics of urban environments. One central feature of urban environments is that they are surroundings that we share with each other and hence their aesthetic outlook belongs to our common world. One may then ask how common, i.e. shared surroundings should be planned, designed and managed? The author claims that an informed aesthetic consensus is needed. Throughout the paper he discusses why it is important to think about a consensus within urban aesthetic decision making in postmodern times, he presents the notion of an informed aesthetic consensus and its importance for aesthetic theory, finally—he explains how it may be applied to democratic processes of urban aesthetic decision making.